Separation of Cu2+ from membrane concentrate by SiO2/3-Aminopropyltriethoxysilane-coated ceramic membrane - Delikanlı, Niyazi Erdem; Harman, B. I.; Yigit, N. O.; Sardohan Koseoglu, T.; Kitis, M.; Koseoglu, H.; Delikanlı, Niyazi Erdem (Springer, 2022)
Concentrate stream of polymeric membranes is a major problem due to the high amount of their pollutant load. However, recoverable precious metal ions are present in the concentrate. In this regard, titania-supported ceramic membranes were modified by mesoporous silica with 3-aminopropyltriethoxysilane to obtain improved separation efficiency for metal recovery from concentrate. Improved separation efficiency for copper ions which were generated from industrial wastewaters was achieved. The modified membrane was characterized by scanning electron microscopy with energy-dispersive X-ray analysis, X-ray fluorescence spectrometer, surface roughness, and contact angle measurements. In experiments with model wastewater concentrates, copper rejection with modified membranes was 18% for the feed concentration of 512 mg/L and 19% for 1280 mg/L. 54% copper rejection for 512 mg/L and 45% copper rejection for 1280 mg/L were obtained with real industrial wastewater concentrates. Membrane separation and membrane surface adsorption mechanisms were discussed. The study showed that modified ceramic membranes can be used effectively for the treatment of membrane concentrate streams and recovery of precious metals. Trial Registration Number and Date: JEST-D-20-01141/14 May 2020.
Keywords: Concentrate Streams; Membrane Coating; Industrial Wastewater; Copper Rejection; Copper Recovery